Meningkatkan kreativitas anak melalui bentuk dasar geometri pada anak kelompok b Tk aisyiyah 58 surakartaTahun ajaran 2015/2016 - Asphriyani, Desi (2016)
Essay. The Faculty of Education, University of Muhammadiyah Surakarta, February, 2016. This study aims to improve children's creativity Group B in Aisyiyah 58 kindergarten Surakarta through learning activities with basic geometric shapes. This research is a classroom action research conducted in two cycles Each cycle consistis of two meetings. This study was conducted collaboratively between researchers and teachers. Subjects in the study were 21 children Group B TK Aisyiyah 58 Surakarta consisting of 10 boys and 11 girls. Object under investigation is the creativity of children. Data collection techniques in this study using observation and field notes. Data were analyzed using comparative and interactive. The results showed that the creativity of children has increased in each cycle. Such improvements can be seen in the initial condition of a child's creativity Group B amounted to 49.3%, the first cycle was 66.5%, and the second cycle of 85.0%. The conclusion of this study, through the basic geometrical shapes can enhance the creativity of children in group B TK Aisyiyah 58 Surakarta Academic Year 2015/2016.